Conservation of phylogeographic lineages under climate change. Issue 1 (10th May 2012) - D'Amen, Manuela; Zimmermann, Niklaus E.; Pearman, Peter B.
ABSTRACT Aim We address the unexplored question of whether the lack of information on intra‐specific diversity inherent in species‐level niche modelling might bias evaluation of the conservation requirements of species and phylogeographic lineages under changing climates. We test for directional biases that might arise due to these methodological differences in ways of assessing risks from climate change. Location The African continent. Methods We identified from peer‐reviewed studies that used both nuclear and plastid markers the distribution of deep phylogeographic divisions within nine species of African mammals and their phylogeographic lineages. We fitted ecological niche models to describe currently suitable, occupied climates and to project the shift of suitable climate to two future time slices. We applied gap analysis to reveal potential changes in the protection of phylogeographic diversity owing to climatic shifts. Results We found that, within species, most phylogeographic lineages differ in the climates they experience and have substantial geographic separation. Models that do not distinguish these subspecific units often fail to identify potential risks of climate change to lineages. Modelled potential effects of climate change on the geographic extent of suitable climate vary in both direction and magnitude. Predictions of the persistence of suitable climate in current protected areas for the resident lineages differ on average by factor of 2 between species and lineage models. Main conclusions Our study develops an original synthetic approach by combining niche modelling, projected climate change, phylogeographic information and gap analysis. We clearly identify the potential benefits of using the new approach to evaluate risks to the conservation of intra‐specific genetic diversity that are posed by climate change. Our results suggest that prudent conservation strategies need to incorporate potential differences in climate tolerance among lineages when planning conservation measures for species confronted with environmental change.